Combinations of siRNAs against La Autoantigen with NS5B or hVAP-A Have Additive Effect on Inhibition of HCV Replication. (29th June 2016) - Mandal, Anirban; Ganta, Krishna Kumar; Chaubey, Binay
Abstract : Hepatitis C virus is major cause of chronic liver diseases such as chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. Presently available direct-acting antiviral drugs have improved success rate; however, high cost limits their utilization, especially in developing countries like India. In the present study, we evaluated anti-HCV potential of several siRNAs targeted against the HCV RNA-dependent RNA polymerase NS5B and cellular factors, La autoantigen, PSMA7, and human VAMP-associated protein to intercept different steps of viral life cycle. The target genes were downregulated individually as well as in combinations and their impact on viral replication was evaluated. Individual downregulation of La autoantigen, PSMA7, hVAP-A, and NS5B resulted in inhibition of HCV replication by about 67.2%, 50.7%, 39%, and 52%, respectively. However, antiviral effect was more pronounced when multiple genes were downregulated simultaneously. Combinations of siRNAs against La autoantigen with NS5B or hVAP-A resulted in greater inhibition in HCV replication. Our findings indicate that siRNA is a potential therapeutic tool for inhibiting HCV replication and simultaneously targeting multiple viral steps with the combination of siRNAs is more effective than silencing a single target.